Contributions to the taxonomy of Dichotomius Hope, 1838 (Scarabaeidae: Scarabaeinae: Dichotomiini): Description of a new subgenus and redefinition of Dichotomius sensu stricto species groups - Jorge Armando Arias-Buriticá; Fernando Zagury Vaz-de-Mello (Revista Brasileira de Entomologia)
ABSTRACT Dichotomius Hope, 1838 is one of the most diverse and abundant genera of dung beetles (Scarabaeidae: Scarabaeinae) in the New World. It congregates about 200 species distributed from the northeastern United States to central Argentina, and is arranged into four subgenera: Dichotomius s. str., Cephagonus Luederwaldt, 1929, Homocanthonides Luederwaldt, 1929 and Selenocopris Burmeister, 1846. The subgenus nominotypical has seen the least progress in its taxonomy, with only 15% of species with information in a recent revision. Therefore, in this paper, using a protocol for taxonomic revision and reviewing the type material and more than 12,000 specimens from 32 entomological collections, we have divided Dichotomius s. str. into two subgenera. We describe Dichotomius (Luederwaldtius) new subgenus to encompass, the smallest species (less than 20 mm), 13 species which previously belonged to D. sensu stricto, four species of Dichotomius (Selenocopris), and several undescribed species. Dichotomius triangulariceps (Blanchard, 1846) is transferred to the subgenus Selenocopris based on characters of the male genitalia. The subgenus Dichotomius s. str., in its new, more restricted sense, is delimited to include approximately 73 species arranged into, 12 species groups, plus two incertae sedis species. For each group, its definition is presented with species composition and geographic distribution. The incertae sedis species, D. agesilaus (Waterhouse, 1891) and D. compressicollis (Luederwaldt, 1929) (lectotype designated) are revised; the following information is presented for them: taxonomic history, species’ citation in published literature, redescription of males and females, list of material examined, photographs of the external morphology, male genitalia, and distribution map.